Perencanaan Anggaran dan Manajemen Madrasah dalam Meningkatkan Efektivitas Tata Kelola Pendidikan Pesantren: Studi Kasus Pondok Pesantren Miftahul Ishlah Tembelok Kota Mataram - Baehaqi; Rahmat Akbar Kurniawan (SEMESTA: Jurnal Ilmu Pendidikan dan Pengajaran, 2026)
This study examines the role of budget planning and madrasah management in improving educational governance at Pondok Pesantren Miftahul Ishlah Tembelok, Mataram, West Nusa Tenggara. It applies a qualitative case study design through institutional document review, literature analysis, and comparative analysis of related studies. The analytical framework integrates School-Based Management, educational budget planning, and Islamic financial accountability based on amanah, siddiq, and syura. Findings show that effective educational governance depends on an integrated budget cycle covering planning, implementation, supervision, and evaluation conducted in a participatory, transparent, and accountable manner. The combination of kiai leadership and modern governance strengthens madrasah managerial capacity. The pesantren cooperative functions as an alternative funding source that supports fiscal independence. It recommends strengthening financial personnel, digitalizing reporting systems, and integrating spiritual values with good governance principles.